Characterization and treatment of water for unconventional oil wells with temporal variability and fracturing fluid type - Kim, Seongyun, author; Omur-Ozbek, Pinar, advisor; Carlson, Kenneth, committee member; Catton, Kimberly, committee member; Dooley, Gregory, committee member (Colorado State University. Libraries, 2017)
Flowback/produced water from unconventional oil and gas wells cannot be optimized without an understanding of water quality which needs to be treated for reuse, the factors to be considered include the temporal variability and different frac fluid types used for hydraulic fracturing. Produced water treatment for reuse is becoming a critical factor for water management surrounding unconventional oil and gas industry. For this research flowback/produced water samples were collected over 200 days from two wells in the Wattenberg Field, located in northeast Colorado. One of the frac fluids had an initial pH greater than 10 and had a guar-based gel. The other frac fluid included a non-guar polysaccharide based polymer and an initial pH less than 6. Total dissolved solids (TDS) and total organic carbon (TOC) analyses were conducted as an indicator for presence of organic and inorganic solids, and the data was compared with key ions (barium, calcium, chloride, magnesium, sodium, strontium, boron and iron) with the different frac fluid types. High values of the coefficient of determinant (over 0.85) were observed between TDS and the key ions, showing that significant positive correlations between two. Despite the significant initial pH differences, the concentrations of calcium, chloride, sodium and strontium were statistically equivalent between the two frac fluids. A mass balance approach was applied to evaluate the quantity of mass of injected additives that was recovered over the 200-day period. Zirconium, potassium and aluminum were selected due either to the lack of contribution from the formation (Zr, Al) or the conservative (non-reactive) nature of the ion (K). Recoveries of these ions ranged from 3 % to 33 % after 200 days, and notable differences were observed between frac fluids. The fraction of cross-linking chemical (Zr) recovered was significantly less for the residue-free polysaccharide-based fluid than the derivatized guar-based fluid. It is hypothesized that the polysaccharide-based Zr cross-linked gel is broken down more completely than the guar-based gel, releasing the Zr metal with subsequent precipitation in the formation. Another study conducted for this dissertation involved the analysis and treatment of produced water samples from three wells that were fractured with different fracturing fluid types over 63 days. TOC analysis showed significantly higher organics composition in produced water from wells fractured by the gel and hybrid fluid (943-1,730 mg/L) compared to the well fractured by the slickwater (222-440 mg/L). TDS levels increased with time, varying from roughly 18,000 mg/L to 30,000 mg/L between 1 to 63 days at each well. Liquid chromatography–mass spectrometry (LC-MS) was applied to characterize the organic matters and similar mass spectra were observed from each well with no temporal trend. Chemical equilibrium modeling was used to predict the precipitation of metals from produced water mixed with groundwater. Chemical coagulation was successfully performed for reducing the turbidity from produced water samples at each well. LC-MS was performed to study the compositions of frac fluid prepared with fresh water (FWA) only and frac fluid prepared with recycled water (RWA) mixed with fresh water. Ethylene oxide and propylated glycol functional units were observed from both FWA and RWA samples. Qualitative analysis from FWA and RWA was performed through Agilent qualitative analysis software B.06.00 based on the exact mass of the chemical compound. Van Krevelen diagram proved FWA and RWA show highly saturated and low degree of oxidation of organic compounds. Kendrick mass defect (KMD) from ethylene oxide was below 0.1 while KMD analysis from propylated glycol were close to 1. FWA showed 32.3 average carbon number and 9.8 double bond equivalent and RWA showed 31.5 average carbon number and 9.5 double bond equivalent. For the last phase of this research, produced water samples were treated by electrocoagulation (EC), ultrafiltration (UF), granular activated carbon (GAC) and reverse osmosis (RO) in series. Total dissolved solids (TDS), total organic carbon (TOC), dissolved organic carbon (DOC), BTEX, total petroleum hydrocarbons (TPH), turbidity, propylene glycol, ethylene glycol and ethylene glycol monobutyl ether were measured after each treatment. Gas chromatography–mass spectrometry (GC-MS) with solid phase extraction (SPE) method was applied to detect propylene glycol (PG), ethylene glycol (EG) and ethylene glycol monobutyl ether (EGME) in the samples. EGME was not detected in any produced water samples. PG concentration was between 0.07ug/ml to 5.39ug/ml and EG ranged from 0.07 ug/ml to 5.52ug/ml. GAC removed both PG and EG for acceptable drinking water criteria. EC was effective at removing both turbidity (85%) and TPH (80%) and most of turbidity and 90% of TPH were removed after UF. This study confirmed that almost 95% of BTEX, TOC, and DOC in produced water samples were removed by GAC. GAC contributed approximately 15% of TDS removal while RO removed 90% of TDS (2550mg/L) which is still high for reuse for various purposes.